From community to consumption new and classical themes in rural sociological research - World Congress of Rural Sociology 2008 : Goyang, South Korea); Bonanno, Alessandro (Bingley, U.K. : Emerald, 2010)
This edited book contains salient papers presented at the XII World Congress of Rural Sociology held in South Korea in 2008. These papers have been selected for their quality and have undergone a peer review process. The rationale behind this book rests on the desire to share the wealth of research presented at the World Congress with interested individuals who could not attend the event and it reflects the empirical work and thinking characterizing contemporary rural sociology. As this sociological sub-discipline evolves along with society and the rural world, it appears of paramount importance to make available ground-breaking research to the international scientific community. Rural sociology is changing and this volume testifies of this change by documenting the introduction of new themes of research as well as the evolution of established ones. In this regard, it provides a unique and uniquely international view of the most recent advanced production in rural sociology. The volume consists of eighteen chapters representing original pieces of research and an introduction that frames them in the context of the evolution of the discipline.
Introduction / Alessandro Bonanno, Mark Shucksmith, Raymond Jussaume, Hans Bakker, Yoshio Kawamura -- I have seen the future and it works! : how joint farming may solve contradictions between technological level and farm structure in Norwegian dairy production / Reidar Almås -- New peasantries and alternative agro-food networks : the case of Réseau Semences Paysannes / Alessandra Corrado -- The development of alternative production and consumption activities related to food safety and security and associated gender issues / Hitomi Nakamichi -- The role and possibilities for subsistence production : reflecting on the experience in Japan / Keiko Yoshino -- The globalization of the poultry industry : Tyson Foods and Pilgrims Pride in Mexico / Douglas H. Constance, Francisco Martinez and Gilberto Aboites -- Studying fertility behavior of farm population as a contribution to understanding overall low fertility trends : the case of Slovenia / Majda Cernic Istenic -- State and market : the politics of development, peasantization, and agrarian restructuring in Northern Lao PDR / Jamaree Chiengthong -- Without categories and classifications : rural as a social expression / Loka Ashwood -- Rural community in a globalizing world / Josefa Salete Barbosa Cavalcanti -- Italian immigrants and the built environment in rural Australia / Kirrily Jordan, Branka Krivokapic-Skoko and Jock Collins -- The regenerative power of older migrants? : a case study of Hokkaido, Japan / Kayo Murakami, Rose Gilroy and Jane Atterton -- Making device for sustainable agricultural systems : a case study of Japanese farmers markets / Tadahiro Iizaka and Fumiaki Suda -- Direct sales suit producers and consumers interests in Vietnam / Paule Moustier and Nguyen Thi Tan Loc -- Participation of the state in the distribution of food to urban areas and possible implications for the Venezuelan agro food sector / Agustín Morales -- Capacity building for the environment : forest policy and management in southeastern Europe / Sabine Weiland -- Histories and continuities of water governance in Northern Ghana / Jennifer Hauck and Eva Youkhana -- Gender, bodies and ethnicity in rural places : settlement experiences of immigrant women in rural Victoria / Gayle Farnsworth -- Women farmers networking in Japan : a case study of a pioneering network / Juri Hara-Fukuyo.
Print version record
Keywords: Social Science -- Sociology -- Rural; Social Science -- Anthropology -- General; Sociology; Rural planning; Sociology, Rural -- Congresses